Нанофотонні сенсори в медицині та екології - Сніжко, Д. В.; Рожицький, М. М.; Бих, А. І. (ХНУРЭ, 2009)
The work contains review of existing nanophotonic sensors that includes analysis of existing fabrication techniques, nanomaterials and application areas in medicine and ecology. The prospects of application of quantum dots, Langmuir-Blodgett technique and electrogenerated chemiluminescence effect for development of nanophotonic sensors intended for liquid media assay in medicine and ecology are considered.
Keywords: нанофотонний сенсор; сенсор в медицині